2002
DOI: 10.1038/417299a
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog regulates cell growth and proliferation by inducing Cyclin D and Cyclin E

Abstract: Although mutations that activate the Hedgehog (Hh) signalling pathway have been linked to several types of cancer, the molecular and cellular basis of Hh's ability to induce tumour formation is not well understood. We identified a mutation in patched (ptc), an inhibitor of Hh signalling, in a genetic screen for regulators of the Retinoblastoma (Rb) pathway in Drosophila. Here we show that Hh signalling promotes transcription of Cyclin E and Cyclin D, two inhibitors of Rb, and principal regulators of the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
288
4
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 394 publications
(304 citation statements)
references
References 28 publications
9
288
4
3
Order By: Relevance
“…Cyclin D1 promotes cell-cycle progression through G 1 /S phase transition and since cyclin D1 is expressed at low levels in slowly dividing reserve chondrocytes, but at high levels in rapidly dividing columnar chondrocytes [Yang et al, 2003] it was suggested that cyclin D1 mediates Ihh-dependent proliferative effects. This is supported by studies in Drosophila where Hh signaling directly induces cyclin D transcription through Ci [Duman-Scheel et al, 2002]. Similarly, Shh induces cyclin D expression in order to sustain cell cycle progression in mammalian neuronal precursor cells [Kenney and Rowitch, 2000].…”
Section: Ihh Directly Promotes Chondrocyte Proliferationmentioning
confidence: 82%
“…Cyclin D1 promotes cell-cycle progression through G 1 /S phase transition and since cyclin D1 is expressed at low levels in slowly dividing reserve chondrocytes, but at high levels in rapidly dividing columnar chondrocytes [Yang et al, 2003] it was suggested that cyclin D1 mediates Ihh-dependent proliferative effects. This is supported by studies in Drosophila where Hh signaling directly induces cyclin D transcription through Ci [Duman-Scheel et al, 2002]. Similarly, Shh induces cyclin D expression in order to sustain cell cycle progression in mammalian neuronal precursor cells [Kenney and Rowitch, 2000].…”
Section: Ihh Directly Promotes Chondrocyte Proliferationmentioning
confidence: 82%
“…44 Recently, the transcription factor Cubitus interruptus (Ci) was shown to mediate the effects of Hedgehog (Hh) signalling on cell growth and proliferation in the wing disc by direct binding to the Cyclin E promoter. 45 In addition, the Caudal (CAD) homeodomain protein was shown to bind the dE2F promoter in vitro, and CAD binding sites in the dE2F promoter are required for expression of dE2F in living flies. 46 These results most clearly demonstrate that developmental genes like Cad, Hh and Hox can directly regulate cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, the molecular basis by which hedgehog accelerates the cell cycle, via the induction of cyclin D and cyclin E, has been reported recently. 40 Nevertheless, Ihh stromal cells, in which Ihh should work in a paracrine and/or autocrine fashion, did not exhibit growth acceleration. Moreover, they did not lose contact inhibition either in serum-free conditions or in LTC medium.…”
Section: Discussionmentioning
confidence: 99%